Löfgrens Syndrome: Acute Variant of Sarcoidosis - Haque, M Azizul; Mostafa, M Golam; Ekram, ARM Saifuddin; Tarafdar, AKM Shohidur Rahman (Journal of Medicine, 2010)
Löfgren’s syndrome is an acute form of sarcoidosis that is characterized by erythema nodosum, bilateral hilar lymphadenopathy accompanied by arthritis or arthralgia. We are reporting a 32 year old male with Löfgren’s syndrome and then the literature is reviewed. Keywords: Löfgren’s syndrome; sarcoidosis; erythema nodosum; hilar lymphadenopathy; Bangladesh DOI: 10.3329/jom.v11i2.5472 J MEDICINE 2010; 11 : 193-195